A Role of Physical Activity in Patients with Systemic Lupus Erythematosus – A Literature Review - Staniszewska, Izabela; Baran, Milena (Quality in Sport, 2024)
Introduction: Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disease of unknown cause. Inflammation and immune-mediated damage to multiple organ systems are the hallmarks of this condition. It is capable of affecting virtually every organ of the body, including but not limited to the hematologic, kidney, mucocutaneous, musculoskeletal, and kidney systems. Immunologic abnormalities, specifically the production of numerous antinuclear antibodies Purpose of work: Collect information on the impact of physical exercise and diet on SLE patients and the possibilities of their therapeutic use. Summary: Being active helps patients with SLE maintain a lower body weight, improve their mental state, relieve their fatigue, and increase their general satisfaction. There are some findings that indicate that physical activity is not as important in therapy for patients with SLE as adding exercise to the basic treatment program. Nevertheless, physical activity is beneficial for the overall well-being of individuals, regardless of whether they have SLE or not. Therefore, it is recommended that patients with SLE engage in physical activity, as it has been widely acknowledged to have significant positive health benefits.